Accelerated grain refinement during accumulative roll bonding by nanoparticle reinforcement - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Scripta Materialia, 2011)
Ceramic nanoparticles produced by comminution are introduced homogeneously during accumulative roll bonding (ARB) in aluminium AA1050A by airgun spraying from a stabilized aqueous suspension. In the so-produced nanoparticle-reinforced ultrafine-grained material, acceleration of microstructural evolution during the early ARB cycles as well as reduced grain sizes at higher cycles are observed, both caused by additional local straining around the embedded nanoparticles and accompanied by further strengthening. The presented method of nanoparticle application allows homogeneous as well as graded particle distributio

Asymmetric accumulative roll bonding of aluminium-titanium composite sheets - Hoi Pang Ng; Przybilla, Thomas; Schmidt, Christian; Lapovok, Rimma; Orlov, Dmitry; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Aluminium–titanium (Al/Ti) composite sheets were fabricated via asymmetric accumulative roll bonding (AARB), which capitalises on additional shear to enhance plastic deformation. Multi-layers of Al alloy (AA1050) and commercially-pure Ti sheets were alternatively stacked and rolled-bonded with varied roll diameter ratios (dr) ranging from 1 to 2, for up to four passes. Annealing of selected composite sheets was subsequently carried out at 600 °C for 24 h to compare the rates of solid-state diffusion reactions between Al and Ti components. Mechanical tests revealed that both tensile strength and ductility of the sheets increase systematically with dr. The microstructures and the Al/Ti interfaces of the sheets were analysed in detail using TEM, SEM and FIB techniques. It is shown that not only does AARB lead to a more refined grain size of the Al matrix but also it promotes the development of a nanostructured surface layer on Ti that comprises crystallites of 50–100 nm in size, which is otherwise absent in the case of symmetric ARB (i.e. dr=1). The AARB-processed sheets exhibit a larger thickness of the interdiffusion layer at the Al/Ti interfaces than the counterparts processed via the symmetric ARB route, the difference being in excess of 15%. The effects and the implications of AARB processing on mechanical behaviour and diffusion kinetics are discussed with respect to the microstructural evolutions.
WW1::955

Asymmetric accumulative roll bonding of aluminium–titanium composite sheets - Hoi Pang Ng; Przybilla, Thomas; Schmidt, Christian; Lapovok, Rimma; Orlov, Dmitry; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Keywords: Transmission electron microscopy; Asymmetric accumulative roll bonding; Al–Ti; Mechanical properties; Diffusion

Design of graded materials by particle reinforcement during accumulative roll bonding - Schmidt, Christian; Ruppert, Mathis; Höppel, Heinz Werner; Nachtrab, Frank; Dietrich, Anja; Hanke, Randolf; Göken, Mathias (Advanced Engineering Materials, 2012)
Graded distributions of copper particles in ultrafine-grained aluminium sheets are produced by accumulative roll bonding and particle reinforcement. The metallic copper particles are sprayed on the sheet surfaces under variation of spray distance and/or relative velocity of the spray gun to the sheet. Therewith, the particle content could be varied by a factor of three. After solutionizing, the successful gradation is clearly proven by tensile tests showing a steady and monotonous gradient along the rolling direction. By a systematic analysis of the spraying process, the particle content profile is calculated. Accuracy of the calculation is confirmed by electrical resistivity measurements. The presented method enables the production of tailored sheets by graded particle reinforcement. The graded sheets are also used for basic investigation of materials properties along graded compositions.
WW1::920

Formability of ultrafine-grained AA6016 sheets processed by accumulative roll bonding - Hausöl, Tina; Schmidt, Christian; Maier, Verena; Böhm, Wolfgang; Nguyen, Manh Hung; Merklein, Marion; Höppel, Heinz Werner; Göken, Mathias (Key Engineering Materials, 2012)
Aluminium alloy AA6016 was accumulative roll bonded up to eight cycles in order to produce an ultrafine-grained microstructure. The formability of these sheets was investigated by means of bending tests. Furthermore the influence of a local laser heat treatment at the bending edge is observed. The strength of the UFG samples is increased by a factor of around two compared to the conventionally grained T4 condition which also results in up to 50 % higher punch forces needed for bending of ARB processed samples. An anisotropic bending behaviour is observed. By applying a tailored laser heat treatment along the bending edge prior to the bending tests a local recrystallization and recovery at the deformation zone of the samples is achieved. Thus, ductility is increased locally whereby bending to an angle of 80° is possible with lower forming forces compared to the non-heat treated specimens. The results are compared to previous studies on mechanical properties and formability investigations of ARB processed AA6016.
WW1::929

Grain refinement and deformation mechanisms in heterogeneous ultrafine-grained materials processed by accumulative roll bonding - Göken, Mathias; Höppel, Heinz Werner; Hausöl, Tina; Bach, Jochen; Maier, Verena; Schmidt, Christian; et al. (Nanometals - status and perspective, 2012)
Grain refinement by severe plastic deformation is nowadays intensively used to process pure metals and alloys. These ultrafine-grained and homogeneous materials show already a great potential concerning their mechanical properties. Recently, heterogeneous ultrafine-grained materials consisting of different metals or different alloys became also very attractive. A very promising production process for such multicomponent materials is accumulative roll bonding (ARB) which allows producing laminates with finely distributed micrometer-sized layers. Interesting heterogeneous materials can also be produced by particle incorporation in the ARB process. Hard ceramic particles lead to additional grain refinement of the surrounding metal matrix by flow around the spherical particles. Similar extra grain refinement processes occur also at the interfaces in heterogeneous laminates. Although the deformation mechanisms in such UFG materials have been investigated quite intensively, a generally accepted view is still missing. Especially the question if grain boundary sliding or thermally activated dislocation processes are the dominant deformation mechanism has to be clearly answered. It is generally accepted that the strain rate sensitivity of nanomaterials is significantly enhanced compared to coarse grained materials, which probably is the dominant contribution to the often reported enhanced ductility. In the literature some indications can be found that also grain boundary sliding occurs under specific conditions and is sometimes considered as the dominant deformation mechanism in nanomaterials. Here, different arguments based on macroscopic deformation experiments such as strain rate jump tests and fatigue tests are discussed. The results show that thermally activated dislocation processes at the grain boundaries are the dominant deformation mechanisms in UFG materials. In addition nanoindentation experiments and focused ion beam investigations indicate that grain boundary sliding occurs only at free surfaces but not in the bulk volume of ultrafine-grained materials. This leads to the suggestion that thermally activated deformation processes at grain boundaries are dominant in ultrafinegrained materials with grain size of some hundred nanometers.
EAM Import::2019-03-13

GRAIN REFINEMENT AND DEFORMATION MECHANISMS IN HETEROGENEOUS ULTRAFINE-GRAINED MATERIALS PROCESSED BY ACCUMULATIVE ROLL BONDING - Göken, Mathias; Höppel, Heinz Werner; Hausöl, Tina; Bach, Jochen; Maier, Verena; Schmidt, Christian; Amberger, D. (2012)
Grain refinement by severe plastic deformation is nowadays intensively used to process pure metals and alloys. These ultrafine-grained and homogeneous materials show already a great potential concerning their mechanical properties. Recently, heterogeneous ultrafine-grained materials consisting of different metals or different alloys became also very attractive. A very promising production process for such multicomponent materials is accumulative roll bonding (ARB) which allows producing laminates with finely distributed micrometer-sized layers. Interesting heterogeneous materials can also be produced by particle incorporation in the ARB process. Hard ceramic particles lead to additional grain refinement of the surrounding metal matrix by flow around the spherical particles. Similar extra grain refinement processes occur also at the interfaces in heterogeneous laminates. Although the deformation mechanisms in such UFG materials have been investigated quite intensively, a generally accepted view is still missing. Especially the question if grain boundary sliding or thermally activated dislocation processes are the dominant deformation mechanism has to be clearly answered. It is generally accepted that the strain rate sensitivity of nanomaterials is significantly enhanced compared to coarse grained materials, which probably is the dominant contribution to the often reported enhanced ductility. In the literature some indications can be found that also grain boundary sliding occurs under specific conditions and is sometimes considered as the dominant deformation mechanism in nanomaterials. Here, different arguments based on macroscopic deformation experiments such as strain rate jump tests and fatigue tests are discussed. The results show that thermally activated dislocation processes at the grain boundaries are the dominant deformation mechanisms in UFG materials. In addition nanoindentation experiments and focused ion beam investigations indicate that grain boundary sliding occurs only at free surfaces but not in the bulk volume of ultrafine-grained materials. This leads to the suggestion that thermally activated deformation processes at grain boundaries are dominant in ultrafine-grained materials with grain size of some hundred nanometers.

Influence of Nanoparticle Reinforcement on the Mechanical Properties of Ultrafine-Grained Aluminium Produced by ARB - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Materials Science Forum, 2011)
Dispersed nanoparticles are introduced from stabilized suspensions during the accumulative roll bonding process in aluminium AA1050A by air gun spraying up to a final volume fraction of 0.1 % after eight cycles. Additional strengthening caused by particle insertion is observed and strongly depends on the suspension medium and stabilizing agent as both influence interfacial bonding of the particles to the matrix. The particle insertion furthermore results in reduced peel strength of the sheets irrespective of particle material and size caused by a reduction of effective metal to metal bonding area during rolling through the presence of the particle

Maßgeschneiderte partikelverstärkte Verbundwerkstoffe und Werkstoffverbunde hergestellt durch den akkumulativen Walzprozess (ARB) - Schmidt, Christian; Höppel, Heinz Werner; Göken, Mathias (Tagungsband zum 18. Symposium Verbundwerkstoffe, 2011)
Der akkumulative Walzprozess (ARB) bietet die Möglichkeit ultrafeinkörnige Blechwerkstoffe mit interessanten mechanischen Eigenschaften herzustellen. Durch die kontrollierte Einbringung stabilisierter Nanopartikel während des ARB-Prozesses wurde im Rahmen dieser Arbeit gezeigt, dass der ARB-Prozess auch hervorragend dafür geeignet ist, UFG-Verbundwerkstoffe herzustellen und Eigenschaften maßzuschneidern. Bereits ein sehr geringer Anteil keramischer Nanopartikel von 0,1 vol.-% führt durch zusätzliche, lokale plastische Verformung einerseits zu beschleunigter Kornfeinung, wodurch die hohen spezifischen Festigkeiten ultrafeinkörniger Werkstoffe bereits nach zwei statt acht Walzzyklen erreicht werden können. Andererseits kann gegenüber der reinen UFG-Struktur eine zusätzliche Festigkeitssteigerung erzielt werden.
EAM Import::2019-03-12

Particle based alloying by accumulative roll bonding in the system Al-Cu - Schmidt, Christian; et al. (Metals, 2011)
The formation of alloys by particle reinforcement during accumulative roll bonding (ARB), and subsequent annealing, is introduced on the basis of the binary alloy system Al-Cu, where strength and electrical conductivity are examined in different microstructural states. An ultimate tensile strength (UTS) of 430 MPa for Al with 1.4 vol.% Cu was reached after three ARB cycles, which almost equals UTS of the commercially available Al-Cu alloy AA2017A with a similar copper content. Regarding electrical conductivity, the UFG structure had no significant influence. Alloying of aluminum with copper leads to a linear decrease in conductivity of 0.78 µΩ·cm/at.% following the Nordheim rule. On the copper-rich side, alloying with aluminum leads to a slight strengthening, but drastically reduces conductivity. A linear decrease of electrical conductivity of 1.19 µΩ·cm/at.% was obtained.
WW1::895

Tailored heat treated accumulative roll bonded aluminum blanks: failure under bending stresses - Nguyen, H.; Boehm, W.; Tsoupis, Ioannis; Göken, Mathias; Höppel, Heinz Werner; Schmidt, Christian; Hausöl, Tina; Ruppert, Mathis; Merklein, Marion (Production Engineering, 2016)
Ultrafine-grained accumulative roll bonded (ARB) sheet metals of aluminum alloys have a high potential for lightweight construction. The mechanical properties can be enhanced regarding strength and ductility by the combination of ARB and a local heat treatment according to the Tailor Heat Treated Blanks technology. The present investigation focuses on the failure behavior of ultrafine-grained ARB blanks. Due to the low formability of these high-strength ARB metals, a detailed understanding of the failure mechanisms is essential. For this purpose, an established approach to determine the different stages of damage of the material for conventional materials is now applied to multilayered aluminum in the as-received and heat-treated condition. In this context, air bending tests are used to qualify and quantify the bending and forming behavior of ARB sheets of AA1050A and AA6016 aluminum alloys.
Keywords: Tailor Heat Treated Blanks (THTB); Ultrafine-grained microstructure (UFG); Failure; Formability; Bending; Accumulative roll bonding (ARB)

Tailored heat treated accumulative roll bonded aluminum blanks: Microstructure and mechanical behavior - Maier, Verena; Hausöl, Tina; Schmidt, Christian; Böhm, Wolfgang; Hung Nguyen; Merklein, Marion; Höppel, Heinz Werner; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2012)
Aluminum alloy AA6016 was accumulative roll bonded up to eight cycles and investigated regarding formability by bending tests. Due to the limited bendability of accumulative roll bonding (ARB) processed materials, a tailored laser heat treatment was performed along the bending edge before forming. This tailored laser heat treatment causes a local recrystallization and recovery of the bending samples at the deformation zone, which locally increases ductility and allows higher bending angles achievable with lower forming forces. Between the recrystallized heat treated zone and the unaffected ultrafine-grained (UFG) base material, a gradient in grain size with a bimodal region is formed. This observed microstructural profile is confirmed by local mechanical testing measuring the hardness and strain rate sensitivity by nanoindentation techniques.
WW1::947

Tailoring materials properties by accumulative roll bonding - Hausöl, Tina; Maier, Verena; Schmidt, Christian; Winkler, Michael; Höppel, Heinz Werner; Göken, Mathias (Advanced Engineering Materials, 2010)
Accumulative roll bonding (ARB) as a method of severe plastic deformation (SPD) is an interesting established process to produce ultrafine-grained (UFG) sheet materials with high potential for light weight constructions. The ARB process offers a high flexibility for tailored material design. Al_2O_3 particles, carbon fibers and titanium foils are used as reinforcement of aluminum sheets introduced during accumulative roll bonding. Furthermore multicomponent materials are produced by cladding of different aluminum alloys. These sandwich-like structures allow to combine desired properties of the materials involved. Post-ARB heat treatment offers another possibility for tailoring materials properties of graded structures as shown by formation of TiAl_3 in Al/Ti laminates. The tailored materials are investigated by means of SEM, EDX, nanoindentation experiments and tensile testing.
WW1::856